1992
DOI: 10.1159/000109326
|View full text |Cite
|
Sign up to set email alerts
|

[<sup>125</sup>I]lodomelatonin Binding Sites in the Chicken Brain: Diurnal Variation and Effects of Melatonin Injection or Pinealectomy

Abstract: The diurnal variation of [125I]iodomelatonin binding sites in the brain and serum melatonin levels were studied at 4-hour intervals under a 12h:12h light:dark cycle in 5-week-old chicks. There was a diurnal rhythm of [125I]iodomelatonin binding capacities in brain membrane preparations with the peak in the light period and the trough in the dark period. However, a diurnal variation with high levels in the dark and low levels in the light was observed in serum melatonin concentrations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
6
20
0
Order By: Relevance
“…Our results are consistent with earlier findings in the Atlantic salmon and goldfish [11,12]. Kj in the 4 species were in the range of 9-13 pmol/1 and considerably lower than the values in the whole brains of several spe cies of fish (K<j = 35-68 pmol/1) [11,12] and birds (Kd = 165-705 pmol/1) [16,[22][23][24][25] and the pars tuberalis of rats (K^ = 58-60 pmol/1) [17]. The number of 2-[125I]iodomelatonin binding sites (fW ) in brain membrane prepa rations from the salmonid species (10-15 fmol/mg protein) tended to be similar to the fish brains (Bmax = 7-14 fmol/mg protein) Time (min) less than 50% inhibition at 10 nmol/1 AS = Atlantic salmon; AC = Arctic charr; RT = rainbow trout; CS = coho salmon; K| = inhibition constant.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with earlier findings in the Atlantic salmon and goldfish [11,12]. Kj in the 4 species were in the range of 9-13 pmol/1 and considerably lower than the values in the whole brains of several spe cies of fish (K<j = 35-68 pmol/1) [11,12] and birds (Kd = 165-705 pmol/1) [16,[22][23][24][25] and the pars tuberalis of rats (K^ = 58-60 pmol/1) [17]. The number of 2-[125I]iodomelatonin binding sites (fW ) in brain membrane prepa rations from the salmonid species (10-15 fmol/mg protein) tended to be similar to the fish brains (Bmax = 7-14 fmol/mg protein) Time (min) less than 50% inhibition at 10 nmol/1 AS = Atlantic salmon; AC = Arctic charr; RT = rainbow trout; CS = coho salmon; K| = inhibition constant.…”
Section: Discussionsupporting
confidence: 93%
“…6-Chloromelatonin was donated by Eli-Lilly (Indianapolis, Ind., USA); the remainder of the chemicals were purchased from Sigma (St. Louis, Mo., USA). The brain tissue was prepared and assayed using a modified method of Yuan and Pang [16]. Briefly, the frozen tissue was weighed and homogenized in 20 vol umes (w/v) of Tris-HCl buffer (0.05 mol/1; pH 7.4; 4°C), and the homogenate was centrifuged at 44,000 g for 20 min.…”
Section: Brain Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin action on the immune system also showed a diurnal varia tion [31] with the sensitive period recorded in the late afternoon. Studies on the brain tissues have demonstrated that there are diurnal variations [32][33][34][35] in the binding capacity for [l25I]-labelled iodomelatonin with higher lev els at midlight or evening and low levels at middark or morning [32,34,35], In this study, our finding of a diurnal variation in the binding capacity of duck thymus is consistent with the findings in other tissues [32,34,35]. The diurnal variation of melatonin in the blood with peak values in the dark period is inversely related to the binding capacity for Recent studies have shown that melatonin has a modulatory effect on the immune func tion including the cellular immune system [3,[5][6][7]36], The mechanisms of melatonin ac tion on the immune system remain unclear.…”
Section: Discussionmentioning
confidence: 99%